Surgical Management of the Explant Patient: An Update on Options for Breast Contouring and Volume Restoration. Issue 5 (November 2020) - Avashia, Yash J.; Rohrich, Rod J.; Gabriel, Allen; Savetsky, Ira L.
Abstract : Background: Breast implant removal is becoming a common procedure in light of the current events and controversies with silicone breast implants. The authors believe strongly in informing patients about the indications and options regarding both explantation and the management of the secondary breast deformity. Methods: Relevant literature regarding the management of the explant patient was reviewed and organized to provide an update on prior publications addressing the explant patient population. Results: Surgical management options after implant removal include breast contouring and volume restoration. Fat augmentation has been used in both aesthetic and reconstructive breast surgery. Conclusions: The authors review the surgical management for explantation, breast contouring, and autologous fat grafting for volume restoration. In the explant patient, autologous fat grafting serves as a reliable option for volume restoration.